2022
DOI: 10.17507/jltr.1304.13
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the IELTS Reading Comprehension: Implications for Development of EFL Reading Comprehension Instruction

Abstract: Question type and format in reading tasks are essential characteristics that have been proven to affect students' performance. This study aims to investigate the characteristics of questions used in the IELTS reading comprehension tasks, including (1) question types and (2) question formats. The researchers collected 240 reading question items from six test modules in Barron's IELTS Preparation Test, authored by Lougheed (2016). The categorization criteria for different question types were adapted from Nuttall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Marjerison et al (2020) found that high-scoring participants employed expeditious reading strategies to find information, and more thorough reading strategies to find answers to question tasks. Also, a good grasp of reading question type and question format is beneficial to understanding its contents (Yathip & Chanyoo, 2022) and using the most appropriate strategy. Nosrati (2015) conducted a study on IELTS reading test-taking strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Marjerison et al (2020) found that high-scoring participants employed expeditious reading strategies to find information, and more thorough reading strategies to find answers to question tasks. Also, a good grasp of reading question type and question format is beneficial to understanding its contents (Yathip & Chanyoo, 2022) and using the most appropriate strategy. Nosrati (2015) conducted a study on IELTS reading test-taking strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The IELTS reading test evaluates candidates' English reading and comprehension abilities (Yathip & Chanyoo, 2022). Comprising three sections with different text types, the test demands careful reading and answering questions (Basnet, 2021).…”
Section: Ielts Reading Achievementmentioning
confidence: 99%
“…Bibliometric data analysis concerning research topics in foreign language publications reveals a notable prevalence of terms such as “EFL” and “reading instruction” [ 15 ]. Notably, previous investigations have predominantly centered around teachers’ instructional strategies concerning vocabulary acquisition [ 16 , 17 ], reading strategies [ 18 , 19 ], reading comprehension [ 20 , 21 ], and critical thinking skills [ 22 , 23 ]. Moreover, there have been studies examining how EFL teachers conceptualize reading instruction within diverse cultural contexts [ [24] , [25] , [26] ].…”
Section: Introductionmentioning
confidence: 99%